Ms. Marvel: Marvel’s New Model of Islam’s Representation in Popular Culture - Anisa Hanifah; Lili Awaludin; Hasbi Assiddiqi (Universitas Muhammadiyah Barru, 2024)
This research aims to examine the Ms. Marvel (2022) film series as Marvel's new model in representing Islam throughout popular culture's advancement. Ms. Marvel, known as Kamala Khan, is the first Muslim superheroine character to have her own series at Marvel. This research investigates how the creation and development of this character reflects an invention in the representation of religion and diversity in an entertainment industry that is generally dominated by Western narratives. The research method employed a descriptive qualitative analysis utilizing a cultural studies approach to discern Islam’s representation in Ms. Marvel (2022). Supported by representation and ideology theories, this research would not only examine the impact of Ms. Marvel's character on the general perception of Islam in popular culture but also analyze how the entertainment industry in its entirety may serve as a means to construct a more inclusive perception of religious diversity. The results of this research are intended to offer deeper insights into characters' roles such as Ms. Marvel in reimagining representations of Islam in popular culture and to contribute towards readers' comprehension of the entertainment industry's power through inclusive narratives. Therefore, Ms. Marvel as Marvel's new model in representing Islam may change the negative stereotypes and people's perceptions of Islam.